KAJIAN KINERJA PENYULUHAN PERTANIAN DI KECAMATAN SINDANGKASIH, KABUPATEN CIAMIS, JAWA BARAT - CHARINA, ANNE (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
One of the efforts taken to improve agriculture human resources especially farmers, is through agricultural extension activities. The purpose of agricultural extension is to create a competent farm community that is able to create a strong business, with better farming, better business, better living and better enviroment. To realize all that would be required special education efforts through the development of national agricultural extension system that is able to help farmers and other agricultural businesses to improve their livelihoods and improve their welfare.This study aims to examine how the effectiveness of agricultural extension in general is happening in the District Sindangkasih post autonomy, as well as examine the extent of the impact of agricultural extension activities undertaken to contribute to the socio-economic conditions of farmers.This research was conducted in the District Sindangkasih. This district is one of the districts with a large number of people working in the agricultural sector.This study uses a case study to obtain in-depth pattern of the object under study, with the approach of the PRA (Participatory Rural Apprisal) and FGD (Focus Grouf Discussiaon). The informants in this study is agricultural extension, related agencies and authorities, as well as farmers, who know for certain activities in Kec.Sindangkasih counseling. The draft analysis of the data used to answer the research question in this study is to use qualitative descriptive analysis method, by adopting the Kirkpatrick model of evaluation.Based on the calculation Effectiveness of Agricultural Extension in Sub Sindangkasih obtained a score of 77.48%, which is classified in the category of a very good level of effectiveness. The positive impact is felt farmers with agricultural extension include the improvement of knowledge, skills and mindset, particularly related legowo planting system. On the economic changes that may result from an increase in production which impact on increasing farmers' income Keywords: agricultural extension, Effectiveness, Social Economic Impact.